Konsep Pendidikan Agama Islam Tentang Pendidikan Akhlak dalam Keluarga: Studi Kasus Keluarga Fatayat Nu Kec. Pacet Kab. Bandung - Malik, Deden Abdul; Fathurrohman, Asep A; Salsabilah, Iis (CV. Media Publikasi Profesional, 2021)
Moral education is an obligation for every parent in realizing a successor who has an attitude in accordance with Islamic teachings. Moral education plays a role in realizing the nation's generation. In line with that, the era of digitalization has colored the work and learning faced by children, especially the pandemic situation that requires children to carry out online learning. Parents are required to be extra accompanying children in every action to avoid the use of gadgets that are not wise. The purpose of this study was to identify, analyze and explain the concept of Islamic education about moral education in the Fatayat NU family, Kec. Pacet Kab. Bandung. This study uses a descriptive qualitative method by conducting observations, interviews and analyzing data and combining it with several sources obtained. The results of the discussion of this study explain that the perspective of parents regarding obligations to children is only limited to providing education in schools, it is known that there is a lack of application of concepts in educating children's morals, and the main problem of child delinquency is the influence of the development of electronic technology. This study recommends that further research be carried out which is combined with a psychological approach and presents the success of the application.